2017
DOI: 10.1155/2017/6074703
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Tooth Loss in Adults: A 4-Year Population-Based Prospective Cohort Study

Abstract: Objective To verify the incidence of tooth loss in extended age group of adults in 4 years. Materials and Methods The prospective cohort study assessed adults (20–64 years old) between 2011 and 2015, from Piracicaba, São Paulo, Brazil. The dependent variable was cumulative incidence of tooth loss, assessed by difference between missing teeth (M) of decayed, missing, and filled tooth index (DMFT) in 2011 and 2015. Participants were stratified into young (20–44 years old) and older (45–64 years old) adults. Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
2
20
0
3
Order By: Relevance
“…Inclusion criterion was having participated in the baseline independent of actual address. Exclusion criteria were the same as the baseline [12, 13]. Details of calibration process were described in previous publication [13].…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criterion was having participated in the baseline independent of actual address. Exclusion criteria were the same as the baseline [12, 13]. Details of calibration process were described in previous publication [13].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the studies included in this review did not report the location of missing teeth, several studies assessing the incidence of tooth loss have demonstrated that the posterior occluding units are the most affected and the front teeth the least affected (Montandon et al, 2012; Minja et al, 2016); being premolars less affected than molars (Silva-Junior et al, 2017), and this may interfere in the prediction of MD. Thus, future studies should include the location of missing teeth in dental records, considering that the presence of three to four premolars can still provide good mastication function, as well as the presence of removable full or partial dentures (Zhang et al, 2019), fixed dentures and implants (Prithviraj et al, 2014; Neves et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These results reinforce and qualify the need of inversion in the form of oral health care of adults. There is a clear need for prioritization of primary health care in socially excluded areas for the recovery of damages caused by dental caries in the early stages, so that these damages do not result in more complex treatment needs and, mainly, in tooth loss [9]. This stimulus has been verified in Brazil in recent years through the creation of the National Oral Health Policy in 2004, with expansion of the offering of dental services and inclusion of the Oral Health Team in the Family Health Strategy, with appreciation of care at the level of promotion, prevention and recovery of oral problems in the primary health care.…”
Section: Social Exclusion Idexmentioning
confidence: 99%
“…Despite advances in world public health, the incidence of dental caries has not reduced in recent decades and presents uneven distribution in the populations [5][6][7]. In Brazil, despite the reduction of caries experience in the children population [2], this tendency is not seen in other age groups and also presents an increase in older populations such as in adults [8,9].…”
Section: Introductionmentioning
confidence: 99%